공유 지상국을 활용하여 획득한 마이크로중력 과학임무 큐브위성의 운영 결과와 교훈 - 이명규; 박설현; Myung-Kyu Lee; Seul-Hyun Park (우주기술과 응용, 2024)
Currently, investigations in microgravity environments are carried out in a variety of applications, including drop towers, where experiments can be performed for short periods of time, and space stations, where time is not limited. However, producing a microgravity environment for long-term scientific research requires huge development expenditures and efforts. As a result, if the microgravity experiment is carried out on a cubesat, the variety of scientific studies will likely increase even more due to its low cost. The Korea Microgravity Science Laboratory (KMSL) cubesat, which has these features, is a satellite that has carried out microgravity science missions. On March 22, 2021, the KMSL satellite was launched by a Soyuz2.1a from Baikonur in Kazakhstan and operated normally for nearly two months. This article presents results and lessons gained for successfully completing science missions in microgravity based on the KMSL satellite's operational experience. 현재 마이크로중력 환경을 활용한 과학실험은 초 단위 정도의 짧은 시간 동안 실험이 수행 가능한 낙하 탑부터 시간제한이 없는 우주정거장 등 여러 분야에서 수행되고 있다. 하지만 과학 실험에 필요한 긴 시간이 확보된 마이크로중력 환경을 구현하기 위해서는 적지 않은 개발비용과 시간이 소모된다. 따라서 고비용이 수반되는 마이크로중력 환경 실험을 큐브위성에서 수행한다면 저비용 고효율의 이점으로 과학 실험의 다양성과 시간의 제약에서 자유도가 더욱 높아질 것으로 판단된다. 이러한 특장점을 살린 KMSL(Korea Microgravity Science Laboratory) 큐브위성은 마이크로중력 환경에서의 과학 임무를 수행하였던 위성이다. KMSL 위성은 2021년 3월 22일 카자흐스탄 바이코누르 발사기지에서 Soyuz2.1a 발사체에 의해 발사되었고, 약 2개월간 정상적으로 임무를 수행하였다. 본 논문에서는 KMSL 위성의 운영 경험과 발생한 문제에 대한 분석을 바탕으로 마이크로중력 환경에서의 과학 임무를 성공적으로 수행하기 위한 해결책과 교훈을 제시하고자 한다.